2009
DOI: 10.1182/blood-2008-11-191544
|View full text |Cite
|
Sign up to set email alerts
|

The presence of JAK2V617F mutation in the liver endothelial cells of patients with Budd-Chiari syndrome

Abstract: Patients with myeloproliferative disorders are at a high risk of developing thrombotic events. Several investigators have hypothesized that endothelial cell (EC) abnormalities might contribute to this prothrombotic state. Budd-Chiari syndrome (BCS) and portal vein thrombosis have been reported to be associated with JAK2V617F-positive hematopoiesis. We explored whether JAK2V617F was present in ECs in the vessels of polycythemia vera (PV) patients with BCS using laser capture microdissection followed by nested p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 31 publications
5
134
1
5
Order By: Relevance
“…43,44 In PV patients with Budd-Chiari syndrome and portal vein thrombosis, Sozer et al showed that cells with endothelial characteristics lining liver sinusoids and venules were JAK2V617F positive. 45,46 Using an immunodeficient mouse transplant assay system, the same group showed that JAK2V617F-positive CD34 ϩ cells were able to generate endothelial like cells in vivo expressing human JAK2V617F. 47 Endothelial cells express a wide range of adhesion proteins, including integrins and CAMs (ie, cell adhesion molecules).…”
Section: Discussionmentioning
confidence: 99%
“…43,44 In PV patients with Budd-Chiari syndrome and portal vein thrombosis, Sozer et al showed that cells with endothelial characteristics lining liver sinusoids and venules were JAK2V617F positive. 45,46 Using an immunodeficient mouse transplant assay system, the same group showed that JAK2V617F-positive CD34 ϩ cells were able to generate endothelial like cells in vivo expressing human JAK2V617F. 47 Endothelial cells express a wide range of adhesion proteins, including integrins and CAMs (ie, cell adhesion molecules).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of the JAK2 mutation in circulating endothelial progenitor cells and liver endothelial cells of patients with myeloproliferative neoplasms, especially in those with Budd-Chiari syndrome, further supports a role for defective endothelial cells in the pathogenesis of thrombosis in these diseases. 24,25 Finally, the acquired activated protein C resistance observed in ET and PV is also correlated with the JAK2 mutation, especially in homozygotic patients, supporting a prothrombotic role for the mutation. This hypothesis is reinforced by the high plasma tissue factor concentration and low concentrations of protein S, factor II, factor V, and tissue factor inhibitor found in JAK2-positive patients with myeloproliferative neoplasms.…”
Section: 21mentioning
confidence: 98%
“…33 An increased number of prothrombotic circulating endothelial cells are seen among these patients, 34 and interestingly the JAK2V617F mutation is found in these endothelial cells. 35 …”
Section: Pathophysiologymentioning
confidence: 99%